Harry And Dinosaure Roar The Rescue! - "Whybrow, Ian" (Puffin: London, 2011)
Harry thinks he's too old for his bucketful of dinosaurs but they have other ideas. He looked after them when he was little and now they're determined to stick by him ...for life. And Harry is not the only one who's got a lot bigger.
Keywords: English Fiction - Book